EDUKASI PENGENALAN UANG PALSU DAN CARA MEMBEDAKANNYA DENGAN UANG ASLI - Fajar Hidayanto (UII, 2015)
Counterfeit money is an imitation currency that is manufactured without legal approval of government. The manufacture, usage, and distribution of counterfeit moneyis very dangerous for a country economy. Either in the scale of market that have directcontact with society or in a large scale such as inflation. To prevent those, socializationshould be done to each elements of society, including villager. Village that face manyobstacles in accessing information will easily become the target of counterfeit moneycirculation. Therefore, an education about intoduction of counterfeit money and how todistinguish it with real money was proclaimed in a community service activity at DukuhJati, Kulonprogo, Daerah Istimewa Yogyakarta. Results of that education is people atDukuh Jati is be more understanding about counterfeit money and can recognise it. Itscirculation is expected to decline continuously.